Birmingham Mid-Head Resection Periprosthetic Fracture. - Aqil,A; Sheikh,HQ; Masjedi,M; Jeffers,J; Cobb,J (CiOS Clinics in Orthopedic Surgery, 2015)
Total hip arthroplasty in the young leads to difficult choices in implant selection. Until recently bone conserving options were not available for younger patients with deficient femoral head bone stock. The novel Birmingham Mid-Head Resection (BMHR) device offers the option of bone conserving arthroplasty in spite of deficient femoral head bone stock. Femoral neck fracture is a known complication of standard resurfacing arthroplasty and is the most common reason for revision. It is unknown whether this remains to be the case for the BMHR neck preserving implants. We report a case of a 57-year-old male, who sustained a periprosthetic fracture following surgery with a BMHR arthroplasty. This paper illustrates the first reported case of a BMHR periprosthetic fracture. The fracture pattern is spiral in nature and reaches to the subtrochanteric area. This fracture pattern is different from published cadaveric studies, and clinicians using this implant should be aware of this as revision is likely to require a distally fitting, rather than a metaphyseal fitting stem. We have illustrated the surgical technique to manage this rare complication.